E-Selectin Ligands in the Human Mononuclear Phagocyte System: Implications for Infection, Inflammation, and Immunotherapy - Silva, Mariana; Videira, Paula A.; Sackstein, Robert (Frontiers in Immunology, 2018)
The mononuclear phagocyte system (MPS) comprises a network of circulating monocytes and dendritic cells (DCs), and “histiocytes” (tissue-resident macrophages and DCs) that are derived in part from blood-borne monocytes and DCs. The capacity of circulating monocytes and DCs to function as the body’s first-line defense against offending pathogens greatly depends on their ability to egress the bloodstream and infiltrate inflammatory sites. Extravasation involves a sequence of coordinated molecular events and is initiated by E-selectin-mediated deceleration of the circulating leukocytes onto microvascular endothelial cells of the target tissue. E-selectin is inducibly expressed by cytokines (TNF-α and IL-1β) on inflamed endothelium, and binds to sialofucosylated glycan determinants displayed on protein and lipid scaffolds of blood cells. Efficient extravasation of circulating monocytes and DCs to inflamed tissues is crucial in facilitating an effective immune response, but also fuels the immunopathology of several inflammatory disorders. Thus, insights into the structural and functional properties of the E-selectin ligands expressed by different monocyte and DC populations is key to understanding the biology of protective immunity and the pathobiology of several acute and chronic inflammatory diseases. This review will address the role of E-selectin in recruitment of human circulating monocytes and DCs to sites of tissue injury/inflammation, the structural biology of the E-selectin ligands expressed by these cells, and the molecular effectors that shape E-selectin ligand cell-specific display. Additionally, therapeutic approaches targeting E-selectin receptor/ligand interactions, which can be used to boost host defense or, conversely, to dampen pathological inflammatory conditions, will also be discussed.